Towards a commerical microelectrode array based sensor for improved chlorine detection. - Mills, Daniel W. (Cranfield University, 2005)
The commercial development of a disposable aqueous chlorine sensor based on a novel microelectrode array fabrication process is described. Non-conducting poly(o-phenylenediamine) films are firstly used to passivate conductive surfaces. Ultrasonic ablation of passivated electrode assemblies then results in the formation of a plurality of wells to expose the underlying conductive substrate, thereby forming a microelectrode array. Microelectrode arrays produced in this manner can be exploited within many electrochemical sensing applications; however, portable aqueous chlorine detection has been selected by Microarray Limited (the industrial sponsors of this project) as a primary vehicle for launching its generic production technology. The scale of microelectrode array production has been extended from that of individual gold sputtercoated glass slide electrodes - to the simultaneous production of hundreds of low-cost screen printed carbon-ink based sensors. A focus has been directed at all stages towards permitting the cost-effective large-scale mass production of sensors with a view to challenging existing portable aqueous chlorine measurement technologies both in terms of performance and unit cost. Based on volume batches of 250,000, it has been calculated that Microarray Limited sensors can be manufactured for a unit cost of approximately 2.5 pence, sufficiently low to provide scope for a competitive yet profitable sale price. The Microarray Limited aqueous chlorine detection system has improved the limit of detection from 0.01 ppm to 0.005 ppm total chlorine without sacrificing accuracy. Furthermore, this novel approach to aqueous chlorine detection offers numerous key benefits to the customer including reduced testing time, a more straightforward operation and the elimination of harmful reagents. Product development has been described from an initial concept through to a pre-production phase. The development of an innovative generic sensor packaging technology is also described.